The organizational structure of an intensive care unit influences treatment of hypotension among critically ill patients: A retrospective cohort study - Boone, M. Dustin (J Crit Care, 2016)
PURPOSE: Prior studies report that weekend admission to an intensive care unit is associated with increased mortality, potentially attributed to the organizational structure of the unit. This study aims to determine whether treatment of hypotension, a risk factor for mortality, differs according to level of staffing. METHODS: Using the Multiparameter Intelligent Monitoring in Intensive Care database, we conducted a retrospective study of patients admitted to an intensive care unit at Beth Israel Deaconess Medical Center who experienced one or more episodes of hypotension. Episode(s) were categorized according to the staffing level, defined as high during weekday daytime (7am–7pm) and low during weekends or nighttime (7pm–7am). RESULTS: Patients with a hypotensive event on a weekend were less likely to be treated compared to those that occurred during the weekday daytime (p=0.02). No association between weekday daytime versus weekday nighttime staffing levels and treatment of hypotension was found (RR 1.02; 95% CI 0.98–1.07). CONCLUSION: Patients with a hypotensive event on a weekend were less likely to be treated than patients with an event during high-staffing periods. No association between weekday nighttime staffing and hypotension treatment was observed. We conclude that treatment of a hypotensive episode relies on more than solely staffing levels.